2001
DOI: 10.1128/jcm.39.1.394-397.2001
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Resistance to Metronidazole and Clarithromycin in Helicobacter pylori Strains in Children

Abstract: The aim of the study was to evaluate the prevalence of resistance to amoxicillin, metronidazole, and clarithromycin before treatment of Helicobacter pylori infection in children and to assess the evolution of resistance with time. The study was carried out between 1994 and 1999 with 150 H. pylori-positive children through gastric culture (antimicrobial susceptibility) and histology. All cultured H. pylori strains were sensitive to amoxicillin, 64 (43%) were resistant to metronidazole, 32 (21%) were resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
40
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 21 publications
12
40
0
3
Order By: Relevance
“…Table 1 shows the MIC 50 s (MICs at which 50% of the isolates tested are inhibited), MIC 90 s, and MIC ranges of, and percentages of resistance to, the three antimicrobial agents tested against the total number of strains. A high percentage of clarithromycin-resistant strains was detected among our pediatric strains, similar to other studies (12,25). In some countries resistance is higher in children than in adults (9), although not in others (21).…”
supporting
confidence: 76%
“…Table 1 shows the MIC 50 s (MICs at which 50% of the isolates tested are inhibited), MIC 90 s, and MIC ranges of, and percentages of resistance to, the three antimicrobial agents tested against the total number of strains. A high percentage of clarithromycin-resistant strains was detected among our pediatric strains, similar to other studies (12,25). In some countries resistance is higher in children than in adults (9), although not in others (21).…”
supporting
confidence: 76%
“…The prevalence of metronidazole-resistant strains in children has been reported to be 19% in Portugal (2), 23% in Spain [Lopez-Brea et al, Gut 47(Suppl. 1):A95, 2000], and 43% in France (17). In contrast, a Canadian study has reported that all strains of H. pylori were susceptible to metronidazole (23).…”
Section: Vol 40 2002mentioning
confidence: 84%
“…In Brazil, resistance to amoxicillin has been detected in 29% of strains recovered posttreatment (27). However, many studies have shown that all strains examined are susceptible to amoxicillin (1,17). The clinical significance of amoxicillin susceptibility testing has not been documented (26).…”
Section: Vol 40 2002mentioning
confidence: 99%
“…We have already shown that the rates of resistance to metronidazole and clarithromycin among isolates of H. pylori from children are high before treatment (i.e., 43 and 21%, respectively) (5). No data are available concerning the antimicrobial susceptibility patterns of strains obtained from cultures from children who had failed an initial course of therapy.…”
mentioning
confidence: 99%